2020
DOI: 10.1038/s41598-020-71144-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of bone marrow-derived infiltrating monocytes and resident macrophages to persistent lung inflammation in chronic air pollution exposure

Abstract: Chronic exposure to particulate matter < 2.5µ (PM 2.5) has been linked to cardiopulmonary disease. Tissue-resident (TR) alveolar macrophages (AΦ) are long-lived, self-renew and critical to the health impact of inhalational insults. There is an inadequate understanding of the impact of PM 2.5 exposure on the nature/time course of transcriptional responses, self-renewal of AΦ, and the contribution from bone marrow (BM) to this population. Accordingly, we exposed chimeric (CD45.2/CD45.1) mice to concentrated PM 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…We found that transplanting WT BM into our lincRNA-Cox2 mutant mice completely rescued the neutrophil and cytokine/chemokine phenotype in the BAL (Figure 7B-K). While we aimed to determine if lincRNA-Cox2 functions either through resident (SiglecF+) or recruited (Siglec F-) alveolar macrophages, we found that both populations were composed of >70% donor BM (SFigure 8I-J) indicating that radiation obliterated resident SiglecF+ alveolar cells which become repopulated with donor cells from the bone marrow (Guilliams et al , 2013; Hashimoto et al , 2013; Misharin et al , 2017; Collins et al , 2020; Gangwar et al , 2020). These experiments enable us to conclude that lincRNA-Cox2 expression originating from the bone marrow can function to control immune responses in the lung, since BM derived immune cells transplanted into lincRNA-Cox2 mutant mice are able to rescue the phenotype driven by loss of lincRNA-Cox2 in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…We found that transplanting WT BM into our lincRNA-Cox2 mutant mice completely rescued the neutrophil and cytokine/chemokine phenotype in the BAL (Figure 7B-K). While we aimed to determine if lincRNA-Cox2 functions either through resident (SiglecF+) or recruited (Siglec F-) alveolar macrophages, we found that both populations were composed of >70% donor BM (SFigure 8I-J) indicating that radiation obliterated resident SiglecF+ alveolar cells which become repopulated with donor cells from the bone marrow (Guilliams et al , 2013; Hashimoto et al , 2013; Misharin et al , 2017; Collins et al , 2020; Gangwar et al , 2020). These experiments enable us to conclude that lincRNA-Cox2 expression originating from the bone marrow can function to control immune responses in the lung, since BM derived immune cells transplanted into lincRNA-Cox2 mutant mice are able to rescue the phenotype driven by loss of lincRNA-Cox2 in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…For RNA sequencing, total RNA was sent to Novogene for sequencing on an Illumina NovaSeq platform and analyzed as described earlier. [27] Hyperinsulinemic-Euglycemic Clamp: The hyperinsulinemiceuglycemic clamp experiment was performed as previously described. [28] Briefly, jugular vein-cannulated mice were acclimated to restrainers (3 h per day for 3 days) before the clamp experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The lung has two macrophage populations: alveolar macrophages and interstitial macrophages (IMs), which differ based on origin and function. Alveolar macrophages are long-lived, embryonically-derived cells that self-renew to maintain their population [ 136 ]. In response to injury, bone marrow monocytes also migrate to the lungs and differentiate into macrophages to restore the alveolar macrophage pool.…”
Section: Pulmonary Consequences Of Cannabis Inhalationmentioning
confidence: 99%